Tenageer Behaviors and Teenager Pregnancies in Limakoli Village, Rote Ndao District, East Nusa Tenggara Province, Indonesia - Betty Roosihermiatie; Indah Nur Esti Leksani; Oktarina Oktarina; Marizka Khairunnisa (Pusat Penelitian dan Pengembangan Humaniora dan Manajemen Kesehatan, 2020)
Young marriage still occur in Indonesia. About 0.2% (22,000) teenager 10-14 years were married. Though, Law of marriage the Republic of Indonesia onage requirements are 19 years for men and 16 years for women.Two things for unexpected pregnancy are maintaining or ending a pregnancy by adolescents. The study aimed to determine teenager behaviors and teenager pregnancies in Limakoli village, Rote Ndao District. It was an explorative ethnographic. Inforrmants were selected by snowball sampling. Data were analyzed by thematic analysis. Girls used to do houseworks. Meanwhile, boys had sports in the afternoon. Tenageers got knowledge and information on reproductive health but discussions of pregnancy and the risks were limited. The pregnant teenagers faced gossips and social stigma. One teen pregnacy was faced angry by their parents and families, aborted, quiet, drop out from school. The other teenager covered her second pregnancy, though her parents likely accept her pregnancy. Teenager pregnancies tended not to have antenatal cares. The traditional marriage ‘Terang Kampung’ was not done by underages, likely it included family and extended families. Pregnant teenagers dropped out from schools, in contrast boys did not. Girls had most impact on teenager pregnancies of physical, psychological, and social risks. Hence, an integrative sociocultural intervention for dating with no sexual relations, no adolescence pregnancies and marriage by school, church, primary health center, traditional leaders, village staffs should be developed. Abstrak Pernikahan muda masih terjadi di Indonesia. Sekitar 0,2% (22.000) remaja 10-14 tahun menikah. Padahal, UU Perkawinan Republik Indonesia tentang persyaratan usia adalah 19 tahun untuk pria dan 16 tahun untuk wanita. Dua hal untuk kehamilan yang tak terduga adalah mempertahankan atau mengakhiri kehamilan oleh remaja. Penelitian ini bertujuan menentukan perilaku remaja dan kehamilan remaja di Desa Limakoli, Kabupaten Rote Ndao. Studi ini adalah etnografi eksploratif. Informan dipilih secara snowball sampling. Data dianalisis dengan analisis tematik. Remaja perempuan biasanya melakukan pekerjaan rumah. Sementara, remaja laki-laki berolahraga di sore hari. Remaja memperoleh pengetahuan dan informasi tentang kesehatan reproduksi, tetapi diskusi tentang kehamilan dan risikonya terbatas. Remaja yang hamil menghadapi gosip dan stigma sosial. Seorang remaja hamil menghadapi kemarahan orang tua dan keluarganya, mengalami aborsi, menjadi pendiam, dan putus sekolah. Remaja lainnya menutupi kehamilannya yang kedua, walaupun kemungkinan orang tuanya menerima kehamilannya. Kehamilan remaja cenderung tidak mendapat antenatal care. Perkawinan tradisional 'Terang Kampung' tidak dilakukan oleh anak-anak di bawah umur, kemungkinan karena melibatkan keluarga dan keluarga besar. Remaja yang hamil mengalami drop out dari sekolah, sebaliknya remaja laki-laki tidak. Remaja perempuan memiliki dampak paling besar pada kehamilan remaja terhadap risiko fisik, psikologis, dan sosial. Sehingga perlu dikembangkan, intervensi sosiokultural integratif untuk berpacaran tanpa hubungan seksual, tidak ada kehamilan remaja dan pernikahan, dengan melibatkan sekolah, gereja, pusat kesehatan primer, pemimpin tradisional, staf desa.